Loss of Hepatic CEACAM1: A Unifying Mechanism Linking Insulin Resistance to Obesity and Non-Alcoholic Fatty Liver Disease - Heinrich, Garrett; Ghadieh, Hilda E.; Ghanem, Simona S.; Muturi, Harrison T.; Rezaei, Khadijeh; Al-Share, Qusai Y.; Bowman, Thomas A.; Zhang, Deqiang; Garofalo, Robert S.; Yin, Lei; Najjar, Sonia M. (Frontiers in Endocrinology, 2017)
The pathogenesis of human non-alcoholic fatty liver disease (NAFLD) remains unclear, in particular in the context of its relationship to insulin resistance and visceral obesity. Work on the Carcinoembryonic antigen-related cell adhesion molecule1 (CEACAM1) in mice has resolved some of the related questions. CEACAM1 promotes insulin clearance by enhancing the rate of uptake of the insulin-receptor complex. It also mediates a negative acute effect of insulin on fatty acid synthase activity. This positions CEACAM1 to coordinate the regulation of insulin and lipid metabolism. The phenotype of hyperinsulinemia, insulin resistance, hepatosteatosis and visceral obesity of mice with genetic mutations of Ceacam1 and the protective effect of hepatic CEACAM1 gain-of-function against the metabolic response to dietary fat bolster the significant role of the loss of hepatic CEACAM1 in NAFLD and visceral obesity.